The Spirit and the law - van der Westhuizen, Henco (Verbum et Ecclesia, 2019)
In this article, the relation between a theology of the Spirit and a theology of biblical law is explored. This is performed in reference to the theology of Michael Welker. In the first part of the article, it is shown how the relation between the Spirit and the law, which could be considered to be his main and most unique contribution towards a theology of the Spirit, serves as the framework for his entire theological endeavour. In the third part, his understanding of the law as life-furthering security of expectations is explored in light of reductionist understandings of biblical law, which is examined in the second part. This is followed by an explanation of Welker's in-depth understanding of the biblical law, of Recht , mercy and knowledge of God. It will then be possible to ask about the relation between this differentiated understanding of biblical law and the Spirit. The conclusion asks how Welker's understanding of this relation, which allows for a more complex understanding of the Spirit's role in reality, moves beyond morality. Intradisciplinary and/or interdisciplinary implications: The article's focus is on the theology of Michael Welker, who's understanding of the relation between law and Spirit is the result of intradisciplinary (Old- and New Testament, Historical Theology, Systematic Theology etc.) and interdisciplinary research (law, sociology etc.). The intra- and interdisciplinarity of his understanding of the relation further differentiates discourses caught up in diverse abstractions, dichotomies and dualisms.
Free
Keywords: COLLATERAL security; DOCTRINAL theology; HOLY Spirit; INTERDISCIPLINARY research; JEWISH law; MERCY of God; Michael Welker; OBEDIENCE (Law); SPIRIT; Spirit and justice; Spirit and law; morality; security of expectations